2019
DOI: 10.1093/ecco-jcc/jjz060
|View full text |Cite
|
Sign up to set email alerts
|

Role of Faecal Microbiota Transplantation for Maintenance of Remission in Patients With Ulcerative Colitis: A Pilot Study

Abstract: Objectives To study the role of faecal microbiota transplantation [FMT] in maintenance of remission in ulcerative colitis [UC]. Methods In this pilot study, patients with UC in clinical remission achieved after multi-session FMT were randomly allocated to either maintenance FMT or placebo colonoscopic infusion every 8 weeks, for 48 weeks. The standard of care [SOC] therapy was continued in all patients. The primary endpoint w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
121
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 128 publications
(129 citation statements)
references
References 52 publications
5
121
0
3
Order By: Relevance
“…The present study demonstrated that three rounds of FMT (13,(28)(29)(30). The improved efficacy displayed in the present study may be explained by the modified FMT procedures used, including stool preparation (feces exposure to air for <30 min), microbiota resource (fresh; all FMTs for one patient were derived from the same donor), delivery route (via TET tube; remained in the right lateral position for 30 min to maintain the largest contact area between microbiota and intestines), dosage (150 ml to avoid inducing intestinal peristalsis) and intensity (three times within one week).…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…The present study demonstrated that three rounds of FMT (13,(28)(29)(30). The improved efficacy displayed in the present study may be explained by the modified FMT procedures used, including stool preparation (feces exposure to air for <30 min), microbiota resource (fresh; all FMTs for one patient were derived from the same donor), delivery route (via TET tube; remained in the right lateral position for 30 min to maintain the largest contact area between microbiota and intestines), dosage (150 ml to avoid inducing intestinal peristalsis) and intensity (three times within one week).…”
Section: Discussionsupporting
confidence: 58%
“…Ramai et al (36) reported that the clinical response in patients at 1 month and 3 months after FMT was 74.3 and 51.4%, respectively. A pilot study in India reported 87.1% clinical response, 58.1% endoscopic remission and 45.2% histological remission at week 48 post-FMT (29). The patients with UC treated with FMT in the present study displayed a steroid-free clinical response rate of 84.1 and 77.3% at week 4 and week 12, respectively.…”
Section: Discussionsupporting
confidence: 48%
“…The efficacy of FMT in induction of remission in moderate–severe active UC has been addressed by four high‐quality randomized controlled trials and multiple cohort studies. FMT has been shown to be effective in patients with steroid‐dependent UC, and it may also have a role in long‐term maintenance of remission . Although initial results are exciting, the available trials and cohort studies are small, and results are variable; therefore, efficacy of FMT is not clearly proven.…”
Section: Introductionmentioning
confidence: 99%
“…FMT has been shown to be effective in patients with steroiddependent UC, 5,6 and it may also have a role in long-term maintenance of remission. 7 Although initial results are exciting, the available trials and cohort studies are small, and results are variable; therefore, efficacy of FMT is not clearly proven. Moreover, apart from efficacy; acceptability, tolerability, and safety are equally vital for FMT to gain place in the therapeutic armamentarium of UC.…”
Section: Introductionmentioning
confidence: 99%
“…https://doi.org/10.1101/2020.03. 16.20022293 doi: medRxiv preprint treatment presented a higher tendency to maintain a steroid-free clinical remission and significantly superior to placebo in both endoscopic and histological remission [25] . In view of the above data, multi-session FMT seems to be an effective therapy for maintaining remission in patients with UC.…”
Section: Frequency Factor Influence the Outcomes Of Fmtmentioning
confidence: 97%